Digital Radicalization and Indonesia's Counterterrorism Strategies in Addressing Technology-Based Terrorism - Arini Sabila Hidayatika; Pujo Widodo (Darul Yasin Al Sys, 2026)
Although digital radicalization and technology-enabled terrorism have received considerable scholarly attention, research integrating the dynamics of digital radicalization, Indonesia’s legal framework, and institutional counterterrorism strategies within a unified analytical perspective remains limited. This study aimed to analyze the characteristics of digital radicalization in Indonesia, evaluate the adaptation of the national legal framework to technology-based terrorism, and examine institutional strategies for addressing emerging digital security threats. A qualitative documentary research design was employed, with sources purposively selected from primary legal documents, official government reports, policy publications, and peer-reviewed academic literature relevant to digital radicalization and counterterrorism. Data were collected through systematic document review and analyzed using qualitative thematic analysis involving data reduction, coding, categorization, thematic synthesis, and interpretation. The findings reveal three major themes. First, digital radicalization has transformed terrorism from an organization-centered phenomenon into a digitally mediated process characterized by the online dissemination of extremist content, technology-enabled recruitment, self-radicalization, and increased vulnerability among children and adolescents. Second, Indonesia’s regulatory framework has expanded beyond conventional criminal justice approaches by incorporating preventive governance, institutional coordination, and counter-radicalization policies through Law Number 5 of 2018, Presidential Regulation Number 8 of 2026, and the National Medium-Term Development Plan 2025–2029. Third, Indonesia’s counterterrorism strategy has undergone institutional transformation through the integration of digital surveillance, collaborative governance, digital literacy, counter-narrative initiatives, and community-based prevention programs. The study concludes that addressing technology-based terrorism requires adaptive governance that combines legal reform, cross-sectoral coordination, and preventive digital resilience. The findings contribute to digital counterterrorism scholarship by integrating digital radicalization, regulatory adaptation, and institutional transformation within a single analytical framework. They also provide practical implications for policymakers, law enforcement agencies, cybersecurity institutions, educational organizations, and digital platform stakeholders seeking to strengthen Indonesia’s capacity to respond to evolving technology-driven terrorist threats. Future research should empirically evaluate the implementation and effectiveness of these strategies and compare their application across national contexts.